2014
DOI: 10.1007/s00198-014-2930-z
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide cohort study of hip fractures: time trends in the incidence rates and projections up to 2035

Abstract: The socioeconomic impact of hip fractures will be high in the near future. This study provides a quantitative basis for future policy decisions to serve this need.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 38 publications
2
51
1
Order By: Relevance
“…The incidence of hip fractures in South Korea in 2008-2012 has been similar to those from recent reports from France and Taiwan [5,18] [ Table 2]. Data obtained from advanced countries beginning in the 1990s indicate that previously observed age-specific increases in the incidence of hip fracture have changed.…”
Section: Incidence Of Hip Fracturessupporting
confidence: 84%
See 3 more Smart Citations
“…The incidence of hip fractures in South Korea in 2008-2012 has been similar to those from recent reports from France and Taiwan [5,18] [ Table 2]. Data obtained from advanced countries beginning in the 1990s indicate that previously observed age-specific increases in the incidence of hip fracture have changed.…”
Section: Incidence Of Hip Fracturessupporting
confidence: 84%
“…Recent reports from Taiwan showed that the incidence of hip fracture was decreasing and have yet to increase [18]. Both number and incidence of hip fracture in this study, however, still increased through 2012.…”
Section: Incidence Of Hip Fracturescontrasting
confidence: 59%
See 2 more Smart Citations
“…Thus, an approach that accounts for adults who have multimorbidity and are prescribed multiple medicines is recommended because such population has a higher risk for adverse events and drug interactions [53]. Considering the projected 2.7-fold growth in the number of hip fractures between 2010 and 2035 [54], the fall epidemic must be surveyed regularly, as the identification of risk factors in older people may help with developing individualized fall risk assessments [23] among high-risk seniors. Furthermore, this approach could enhance fall prevention programs to be more efficient and effective to reduce fall-related hospitalizations [12] in the future.…”
Section: Discussionmentioning
confidence: 99%